Relationship Between Gender, Stress, and Quality of Social Support. Issue 4 (August 2021) - Kneavel, Meredith
Background: Research suggests that gender differences exist in both stress and how social support is utilized and that the relationship between stress and social support may not be linear. Methods: An internet survey of n = 1080 participants was conducted evaluating quality and quantity of social support, gender, age, and perceived stress and coping. Results: Reported quality of social support, gender, and age significantly predicted perceived stress and that there was a curvilinear interaction between the quality of social support and gender which significantly predicted perceived stress. Conclusion: The current findings supported Taylor's Tend and Befriend theory that females have higher reported stress levels, a larger support network, and report more quality in their social support. Practitioner points:   Males and females may manifest stress differently in their relationships.  When working with males and females in practice it may be important to understand the depth and brea dth of their social networks and how they utilize those networks.  Females indicate higher levels of stress and greater social support quality.  It is important to understand that one's social network can be an important source of support (a coping mechanism) but that it can also serve as a stressor in some cases.